(3JMaI GdSGFd aj CLhHI GdeSGFds - (3CMeO Hf eMeO Hf GdMSf Hf Ydj Hf eMeO GdYHGSj GdMfaj, CMeO GdYHGSj,J (B901 (3g` s ((3UGdM Hf EHQGgje GdYLeGhi Gdajhei GdeGdci s)
(3ChdgG (B:s
(3GdMeO ddg GdeMjW HeG dOjfG hGdeJaVd HGdgOGjI ai GdHOGjI hGdfgGjI YdjfG GdeJWhd HfgGjI GdcaGjI hcaGjI GdfgGjI s
(3BNQgG (B:s
(3cPG Yf GdeUWai bO LGAfG GdNHQ hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: 1s
(3GdQSGdI YHGQI Yf (B300 (3SDGd SCdgG GdSdWGf bGjJHGis
(3GdfSNI HgG MhGTs
(3GdfSNI ebGHdIs
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3GdeYGQa GdYGeIs